Makna Puasa dalam Tafsir al-Jailani (Studi tentang Penafsiran Syekh Abdul Qadir al-Jailani) - Muhammad Rifa’i (UIN Siber Syekh Nurjati Cirebon, 2017)
Fasting is restraint during the day from things that cancel fasting, accompanied by intentions by the culprit, from dawn to sunrise. This understanding is explained by fiqh scholars. While the meaning of fasting according to Sufism scholars is to resist lust; the five senses; and turn away from other than God. Therefore, research on the meaning of fasting from the side of Sufism is quite interesting to study. This is because of its wider coverage. The interpretation used as the primary data source in this study is the tafsir al-Jailani. This commentary has different characteristics with other Sufism-style interpretations. Among the differences is there is an introduction and closure of each letter and explains the meaning of fasting in three types, namely the Shari'a fasting; the nature (spirituality), and fasting turning away from other than Allah. The purpose of this study is to describe the method of writing Al-Jailani's interpretation, starting from the biography of Sheikh Abdul Qadir al-Jailani; commentary; Sheikh Abdul Qadir al-Jailani's interpretation of the fasting verses and his analysis.